'The Everyday Work of Repair': Exploring the Resilience of Victims-/Survivors of Conflict-Related Sexual Violence. (January 2022) - Natalya Clark, Janine
This interdisciplinary article uses what Das has termed 'the everyday work of repair' as a framework for thinking about resilience. It is not the first to discuss resilience and the everyday. What is novel is the context in which it does so. Extant scholarship on conflict-related sexual violence has largely overlooked the concept of resilience. Addressing this gap, the article draws on semi-structured interviews with victims-/survivors of conflict-related sexual violence in Bosnia and Herzegovina (BiH), Colombia and Uganda to examine what everyday resilience 'looks' like and how it is expressed within and across highly diverse social ecologies. In so doing, it reflects on what everyday resilience means for transitional justice, through a particular focus on hybridity. It introduces the term 'facilitative hybridity', to underscore the need for transitional justice processes to give greater attention to the social ecologies that can crucially support and enable the everyday work of repair and everyday resilience.